TRADITION ISSUE OF THE ETHNOCULTURE OF THE SOUTH ARAL REGION (Konferensiyalar | Conferences, 2023)
One can note the main factors of the nomads who lived in the “Great Steppe” of Eurasia, the emergence of a unique civilization and culture of peasants, their adaptation and “traceless absence”, historical environmental conditions in the ancient world and the Middle Ages, forced relocation (migration) of steppe peasants to the northwest, the hardships of peasant farming, difficult destinies in a nomadic family, harmful traces of merciless wars and various “symbiotic” relationships [1:47]